2019
DOI: 10.17159/2411-9717/2019/v119n3a12
|View full text |Cite
|
Sign up to set email alerts
|

South Africa’s options for mineimpacted water re-use: A review

Abstract: South Africa is a water-scarce country and is currently rated as one of the 30 driest countries in the world, with an average rainfall of 490 mm/a, approximately half of the global average. As an indicator of the degree of regional variability in South Africa's water supply, it has been shown that 70% of all runoff is from approximately 20% of the land area. Regardless of the water scarcity faced in South Africa, our water conservation track record is poor, with an average consumption of 280 L/d per person, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…Irrigation with AMD water generally causes a shift in the parameters of soils, has the potential to positively alter microbial diversity and plays vital roles in the ecology of the rhizosphere of plants through the maintenance of soil health and therefore increasing the yield of crops 75 77 . The decrease in the yield of crops irrigated with treated AMD water could be a function of the important microbe reduction during the process of treatment 6 . Hence, there is a need to evaluate a system where AMD treatment can protect the important microbial communities while removing the harmful substance that plants can translocate from the soil.…”
Section: Resultsmentioning
confidence: 99%
“…Irrigation with AMD water generally causes a shift in the parameters of soils, has the potential to positively alter microbial diversity and plays vital roles in the ecology of the rhizosphere of plants through the maintenance of soil health and therefore increasing the yield of crops 75 77 . The decrease in the yield of crops irrigated with treated AMD water could be a function of the important microbe reduction during the process of treatment 6 . Hence, there is a need to evaluate a system where AMD treatment can protect the important microbial communities while removing the harmful substance that plants can translocate from the soil.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-filtration of the concentrated brine stream, on the other hand, remains crucial, and the concentrated brine stream can be treated in nitrifyingdenitrifying bioreactors (Häyrynen et al, 2009). Application of this technology is the development of an AMD treatment facility near the town of Emalahleni, South Africa, to address the enormous volume of AMD generated by coal mining activities in the region (Grewar, 2019;Santos et al, 2021). The AMD treated at this facility is mostly derived from active and abandoned coal mining activities and is characterized by a high sulfate level and a relatively low metal content.…”
Section: Reverse Osmosis and Nanofiltrationmentioning
confidence: 99%
“…A review was completed on the reuse of treated mine water in South Africa to replace high‐quality water (Grewar, 2019). It was concluded that reuse of treated mine water in crop irrigation was the most suitable option.…”
Section: Recovery Of Resources From Mine Drainagementioning
confidence: 99%